1998
DOI: 10.1111/j.1600-0846.1998.tb00080.x
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal volume changes of the lower legs in healthy males with a profession that requires standing

Abstract: Diurnal volume changes of the lower legs were distributed as a Gaussian curve. A volume increase was common, but not obligatory. A volume increase of the legs was not associated with complaints of the legs or clinically evident oedema. This suggests that a volume increase can be a physiological phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…The reported fatigue can be linked to performing jobs in standing position [35]. Standing for a long period of time causes static contraction mainly in the back and legs.…”
Section: Discussionmentioning
confidence: 99%
“…The reported fatigue can be linked to performing jobs in standing position [35]. Standing for a long period of time causes static contraction mainly in the back and legs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we can conclude that subjects were aware of swelling in their own faces on those occasions when pronounced swelling actually occurred in the upper eyelids; this would explain the strong correlation between perceived and actual swelling. Krijnen et al (1998) reported about measuring the shape of the lower leg and complaints about the legs of 197 male workers with a standing profession. They found that increase in volume of lower leg after work was reported by 42% and the perceptions such as tired and heavy feeling was reported by 52% of respondents.…”
Section: Discussionmentioning
confidence: 99%
“…In the course of a single day, change in shape associated with swelling can arise and subside repeatedly. Previous studies (Murakami et al, 1998;Krijnen et al, 1998;Winkel, 1986;Winkel, 1981;Pottier et al, 1969) have quantitatively measured swelling in terms of change in the circumference and topology of specific areas of the body, particularly the face, legs, hands and fingers. As well as physical change in shape, swelling tends to create fatigue by making the relevant part of the body feel heavy and/or sluggish.…”
Section: Introductionmentioning
confidence: 99%
“…However, Madeleine et al (1998) claimed that both localized muscle fatigue and reduced blood circulation in the lower limbs contribute to the fatigue of lower limbs. Prolonged standing position at workplace was also studied by Krijnen, de Boer, Ader and Bruynzeel (1998) and was able to record a significant increase in mean volume of both legs. Also the study stated that, volume increase of the leg itself may not be a symptom of edema.…”
Section: Literature Reviewmentioning
confidence: 99%